Exposure to Zearalenone During Early Pregnancy Causes Estrogenic Multitoxic Effects in Mice. (March 2017) - Kunishige, Kohji; Kawate, Noritoshi; Inaba, Toshio; Tamada, Hiromichi
Although zearalenone (ZEN; Sigma Chemicals, St Louis, Missouri) is a well-known mycotoxin with estrogenic activity, the toxic effects of ZEN during pregnancy are unknown. This study compared the effects of daily subcutaneous injections of ZEN (2, 4, or 8 mg/kg) with those of 17β-estradiol (E2; [Sigma Chemicals] 0.8, 1.6, or 3.2 μg/kg) in mice. Injections were administered on gestational days (GDs) 1 to 5, the period including implantation which is sensitive to hormonal balance. The effects of ZEN or E2 were evaluated by comparing the number of live fetuses, their weight, and absorbed conceptuses on GD 18, with those in vehicle-treated controls. In addition, implantation, embryos in the oviducts and those in uteri without implantation sites were investigated on GD 5. In mice treated with the highest dose of ZEN or E2, decidual responses and plasma progesterone concentrations were measured on GDs 5 and 6, respectively, and delayed implantation was investigated on GDs 9 and 14. The results showed that treatment with ZEN, in a manner similar to that seen for E2, led to obstruction of essential processes for establishing and maintaining pregnancy, such as embryo migration from oviducts to uteri, the decidual response, and activation of luteal function. Zearalenone also induced delayed implantation and loss of conceptuses and at low doses caused a retarded growth of the fetuses after normal implantation. It was therefore concluded that ZEN causes multiple estrogenic toxic actions when administered during early pregnancy in mice.